Yona of the dawn. 32 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2021)
"Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! The martial arts tournament to show off the Four Dragons begins, and Gija and Jaeha face off against Ju-do and Geun-tae! Meanwhile, Hak is separated from Yona and the Four Dragons, but he has plans to bridge the gap between himself and Yona..."--Back cover.